Drug-related problems in patients with osteoporosis - Ilić, Darko M; Bukumiric, Zoran; Jankovic, Slobodan M. (Vojnosanitetski pregled, 2016)
Background/Aim. Drug-related problems are especially frequent among patients suffering from non-communicable diseases, like osteoporosis, leading to suboptimal treatment response. The aim of this study was to identify drug-related problems in patients with osteoporosis. Methods. This cross-sectional prospective study was conducted in January 2014 on outpatients with osteoporosis from three health facilities in Belgrade, Serbia. The patients included in the study were older than 50 years, and they were offered an anonymous questionnaire with open-ended questions. Results. There were 355 study participants, 329 (92.7%) females and 26 (7.3%) males. The patients who experienced at least one osteoporotic fracture (n = 208) were significantly less adherent to the therapy, less engaged in sports and regular physical activities, and more prone to nutrition with inadequate intake of calcium and vitamin D than patients without fractures (n = 147). Conclusion. The effectiveness of osteoporosis treatment is decreased by several drug-related problems encountered by both physicians and patients. However, the majority of the drug-related problems could be greatly influenced by appropriate educational programs.